Phonological Awareness in Children–The Perspective of Preschool and Primary School Teachers - Perišić, Snežana P.; Minić, Vesna Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Phonological awareness, an aspect of phonological ability, has been identified as a predictor of early reading. Since the acquisition of reading skills depends largely on the teachers who teach this skill and the relationship that is established with the students, it is important to investigate how they perceive children’s phonological awareness, which is an important segment of reading skill. The aim of this study is to analyse the perceptions of preschool and primary school teachers regarding the development of phonological awareness in children attending a preschool program and in children in the first grade of primary school. The study involved 71 participants, namely 34 preschool teachers and 37 primary school teachers. It was conducted in kindergartens and primary schools in the north of Kosovo and Metohija. The research instrument was a questionnaire designed to investigate the attitudes of teachers and educators towards the reading skills of the children they work with. From this questionnaire, 12 statements related to the perception of phonological awareness were extracted. The data collection was conducted online. The results show that teachers have a predominantly positive perception of children’s phonological awareness and that their attitude is not related to the years of professional experience. It is suggested that studies should be carried out that examine the phonological awareness of the children themselves, in addition to the perceptions of the teaching staff, in order to determine whether teachers interpret phonological awareness in a satisfactory manner.